Collective organisational publicness versus privateness in community sport: a national panel study of local authorities. Issue 4 (8th August 2021) - Hodgkinson, Ian R.; Hughes, Paul; Leone, Vitor
ABSTRACT : Research question: The role and merit of publicness versus privateness in community sport provision is hotly contested in the sport management field, but is there a relationship between ownership types in local authorities' community sport provision and sports participation levels? Research methods : The study combines secondary data on sports participation with objective data on ownership types in community sport provision among local authorities in England, between 2009-2015. The panel model examines whether the mix of ownership types in community sport is associated with differences in reported sports participation levels. Results and findings: The study reveals higher collective organisational publicness in community sport is associated with lower sports participation levels among local populations. The opposite is true of higher collective privateness in local authorities' provision, where higher levels of sports participation are observed among local populations. Implications: If local authorities are to influence sports participation levels among their populations, there is a need to better understand how community sport provision should be delivered. Informed by the findings, greater privateness in local authorities' community sport provision is associated with higher sports participation levels.